Typing and Integron Distribution among Multi-Drug Resistance Escherichia coli - AL-Nuaeyme, Husam Ahmed; Ali, Munim R. (Journal for Research in Applied Sciences and Biotechnology, 2024)
The study aimed, through the use of taxonomic associations, to find the genetic relationship between strains of Escherichia coli bacteria in 152 samples of infection symptoms. The results of the susceptibility test for 42 isolates showed that 8 isolates were sensitive to most antibiotics, while 12 isolates had moderate resistance, ranging from 5-8 antagonists, while 22 isolates were resistant to 9-12 antibiotics. Through the use of phylo-group profiling system it was found that the vast majority of Escherichia coli isolates under study have high virulence factors and possess large genomes by belonging to group B2. The results of genotyping using the PCR-Integron system showed that the unty Pable isolates were only... and that the highest percentage was in the first type, which reached... which indicates that there is a relationship between resistance to multiple antibiotics and the presence of introns.